99.4k views
4 votes
22.

Makes s the subject

√(p) \: is \: equals \: to \: \sqrt[r]{w \: - as ^(2)}


1 Answer

5 votes

Explanation:


√(p) = \sqrt[r]{w - {as}^(2) }

Find raise each side of the expression to the power of r

That's


( √(p) )^(r) = (\sqrt[r]{w - {as}^(2) } ) ^(r)

we have


( √(p) )^(r) = w - {as}^(2)

Send w to the left of the equation


( √(p) )^(r) - w = -{as}^(2)

Divide both sides by - a

We have


{s}^(2) = -(( √(p) )^(r) - w)/(a)

Find the square root of both sides

We have the final answer as


s = \sqrt{ -(( √(p) )^(r) - w )/(a) }

Hope this helps you

User Rmbits
by
5.5k points